Is There Room for 'Fear' as a Human Passion in the Work by Adam Smith? - Daniela Parisi (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
The sciences tell us that fears are physical feelings and mental emotions that play a key role in any society. Not many issues related to fear are explored by economists today. The aim of this paper is to go backwards through the history of economic thought, and examine if and how Adam Smith considered fear in his work: in effect, he devoted a great deal of attention to the concept of fear. This paper does not intend to cover the whole of the topic at hand as it would also be useful to investigate the connections between fear and all the other feelings that pervade Smith's thought.
Keywords: B00; B12; 330; Adam Smith; Human Passions; Fear; Sociology; Psychology; Neurosciences